Indoor Air Quality Management and Mitigation Strategies in University Laboratories - MOHAMAD SATAR, NURUL IZZAH; Mohamad Syafiq Syazwan Mustafa, (Progress in Engineering Application and Technology, 2025)
Indoor air quality (IAQ) management is a systematic approach of managing and improving the indoor air quality in universities laboratories. An investigation of indoor air quality (IAQ) management and mitigation in university laboratory settings is conducted utilizing a mixed methods approach that blends bibliometric analysis with quantitative survey methods. This study aims to achieve two primary objectives: It first addresses the identification of potential sources of IAQ problems in university laboratories and the second one was to analyse the mitigation strategy to address these problems. A rigorous bibliometric analysis was conducted using VOSviewer software on 60 research papers published between 2013 and 2023, revealing four main categories of IAQ concerns: Microbiological and biological contaminants, inadequate air circulation and supply, chemical pollutants and indoor particulate matter. To achieve the second objective, a quantitative survey was distributed to 69 respondents from Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh. The most effective strategy used to deal with insufficient air circulation was to perform air balance in ventilation systems (94.4%), while chemical pollutants were dealt with by properly disposing outdated chemicals (93%). Management of microbiological contaminants by regular cleaning using environmentally friendly agents (94%) ranked highest, and removal of particulate matter by local exhaust ventilation systems (95.4%) was deemed best control measure. This analysis synthesizes a wealth of information on advanced IAQ management strategies in university laboratories. The results emphasize the need for proactively managing IAQ in university laboratories, and the need for systematic implementation of successful mitigation strategies. Universities can make academic and research environments healthier, safer by addressing identified sources of pollution and improving air quality practice practices.